The association of diabetes mellitus with neointimal formation following deployment of second-generation drug-eluting stents: an optical coherence tomographic study. Issue 2 (13th October 2020) - Cai, Jin-Zan; Lu, Wen-Qi; Xu, Chen; Gu, Jue; You, Wei; Xu, Tian; Gogas, Bill D.; Jia, Hai-Bo; Ye, Fei
Abstract : Objectives: The purpose of this study was to evaluate the association of diabetes mellitus (DM) with neointimal formation after implantation of second-generation drug-eluting stent (DES) visualized by optical coherence tomography (OCT). Methods: Patients with single de novo coronary artery disease treated with second-generation DES between June 2014 and June 2017 in our department underwent OCT examination at 1-year follow-up and were enrolled in this retrospective study. The primary end point was in-stent mean neointimal thickness (MNT), and secondary end points included uncovered stent strut, minimal lumen area (MLA), neointimal burden, neointimal hyperplasia (NIH) patterns and stent thrombosis (ST) after 1 year of OCT follow-up. Results: A total of 68 patents with DM (DM group) and 216 patients without DM (non-DM group) were enrolled. At 1-year follow-up, the DM group compared with the non-DM group, showed: MNT [160 (85–245) μm vs. 120 (60–220) μm, P = 0.038] and neointimal burden [21.4 (8.3–30.1)% vs. 14.0 (5.7–26.1)%, P = 0.023] to be significantly increased. Concurrently, MLA [4.60 (3.53–6.06) mm vs. 5.76 (4.28–7.20) mm 2, P = 0. 0.002] was significantly reduced. Interestingly, the degree of uncovered struts (7.3 ± 7.1% vs. 7.7 ± 6.7%, P = 0.704), NIH patterns ( P = 0.984), and ST (7.9% vs. 7.4%, P = 0.88) were comparable between the two groups. After propensity score matching, the MNT [160 (90–240) μm vs. 110 (60–220) μm, P = 0.048] and neointimal burden [21.4 (8.3–30.1)% vs. 15.4 (5.6–26.3)%, P = 0.044] remained significantly different in the DM compared to the non-DM group. Conclusion: DM leads to significant increase in MNT and neointimal burden even with second-generation DES, nevertheless stent strut coverage, ST and NIH characteristics remained comparable among the cohorts at 1-year.